Real women have curves [videorecording (DVD)] - Cardoso, Patricia; Ferrera, America, 1984-; Ontiveros, Lupe; Oliu, Ingrid; Lopez, George, 1961-; López, Josefina, 1969- (HBO Video, 2003)
Should she leave home, go to college and experience life? Or stay home, get married, and keep working in her sister's struggling garment factory? It may seem an easy decision, but for 18-year-old Ana, every choice she makes this summer will change her life.